Older adults’ intend to discontinue using an online paid health consultation platform - An, Jing; Shu, Wanting; Xiang, Ziyue; Wan, Kexin (Edelweiss Applied Science and Technology, 2024)
The main objective of this study is to gain a deeper understanding of the factors that influence older adults’ discontinuous usage of online health consultation platforms. A questionnaire was used to collect data from older adults covering aspects including price value, privacy concern, perceived trust, habit, technology anxiety, dissatisfaction and discontinuous usage intention of the older adults with online paid health consultation platforms. The collected data from 254 valid samples were analyzed by SPSS software. The model fitting test of the structural equation model was carried out by AMOS software. The results show that price value, privacy concern, perceived trust, habit and technology anxiety positively impact the dissatisfaction and discontinuation usage intention of adults respectively. These factors will lead to dissatisfaction which positively impact their discontinuous usage of the online paid health consultation platform. This study provides empirical references for the optimization of online paid health consultation platforms. This study also provides valuable suggestions for the government to ensure an online medical service environment and to promote better use of online health consultation platforms by older adults, thereby improving their quality of life and social participation.